Influence of various dietary regimes upon immunity - Djordjević, Brižita; Ivanović, Nevena (Archives of Pharmacy, 2022)
Although it is considered that optimal nutrition could provide all essential nutrients and active compounds, various dietary regimes are often not following the relevant recommendations. On the contrary, nutritional status is closely related to the immune system. Namely, insufficient caloric intake or a lack of a nutrient can primarily weaken the immune response. The gastrointestinal tract plays an essential role in the function of the immune system, which is both the place of absorption of nutrients and the body’s immune defence. Globally, the most prominent cause of immunodeficiencies is undernutrition and starvation, up to 50 % of undeveloped countries’ populations. Undernutrition negatively affects both innate and adaptive immunity; considering these facts, it is clear that a prolonged low caloric intake could affect immunity adversely. Since the sixties, World Health Organisation has considered relations between nutrition and immunity, and nutritional immunology is a newer scientific discipline. Later, the precise relationship between low protein intake and lymphoid tissue involution was defined. Generally, the deficiencies of energy, proteins, iron, iodine, vitamin A, zinc and calcium are the most common. It is estimated that every third person is being affected globally. Prolonged hypercaloric intake and resulting obesity could also exhibit immunocompromising effects through inflammation and hyperactivation of the immune system. The negative impact on the immune system could also be provoked by intense physical activity, infective agents, and emotional stress.